1998
DOI: 10.3354/meps167037
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria in coral reef water types:removal of cells, stimulation of growth and mineralization

Abstract: Water samples were collected at a fringing coral reef in overlying water, in bottom water between corals and in crevices under coral colonies, and analyzed for nutrient concentrations, bacterial numbers and production. We found decreasing bacterial densities from overlying water through bottom water into crevices (range 9 to 2 X 105 ml-l). Bacterial specific growth was enhanced in reef crevices (range 0.005 to 0.04 h-'). Although bactenal growth was enhanced, bacterial numbers were reduced, showing a transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 24 publications
3
70
0
Order By: Relevance
“…A similar discrepancy exists in the literature for bacterioplankton, with evidence for corals enhancing reef bacterial density (Van Duyl and Gast, 2001;Seymour et al, 2005aSeymour et al, , 2005b or reducing reef bacterial density (Ayukai, 1995;Gast et al, 1998). Many previous studies of DOC and bacterioplankton have focused on atoll lagoon systems with relatively long residence times and potential accumulation of organic material, explaining the widespread perception that reefs exhibit elevated levels of organic matter and bacteria (Linley and Koop, 1986;Yoshinaga et al, 1991;Torréton et al, 1997;Sakka et al, 2002).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A similar discrepancy exists in the literature for bacterioplankton, with evidence for corals enhancing reef bacterial density (Van Duyl and Gast, 2001;Seymour et al, 2005aSeymour et al, , 2005b or reducing reef bacterial density (Ayukai, 1995;Gast et al, 1998). Many previous studies of DOC and bacterioplankton have focused on atoll lagoon systems with relatively long residence times and potential accumulation of organic material, explaining the widespread perception that reefs exhibit elevated levels of organic matter and bacteria (Linley and Koop, 1986;Yoshinaga et al, 1991;Torréton et al, 1997;Sakka et al, 2002).…”
Section: Discussionmentioning
confidence: 59%
“…Together these observations are notable because they indicate that reef physical and biological processes work rapidly in maintaining a planktonic microbial ecosystem fundamentally altered from the surrounding oceans (residence times of Moorea's reefs have been estimated on the order of hours to days; Delesalle and Sournia, 1992;Hench et al, 2008;Lenhardt, 1991). The potential for reefs to rapidly alter the density of bacterioplankton is well supported by studies reporting both depletion of bacterioplankton in reef water columns relative to oceanic waters (Ayukai, 1995;Gast et al, 1998) and enhanced removal of bacterioplankton biomass with proximity to reef benthic organisms (Scheffers et al, 2004;Houlbreque et al, 2006;Genin et al, 2009).…”
Section: Discussionmentioning
confidence: 71%
“…It also implies rapid nitrification and the involvement of marine symbioses equipped to facilitate nitrification, such as corals and sponges (Fiore et al 2010). Several smaller scale studies have suggested that gross releases of dissolved inorganic nitrogen within coral cavities can be explained by rapid uptake of phytoplankton by suspension-feeding organisms (Gast et al 1998;Richter et al 2001;Scheffers et al 2004). In this study, phytoplankton uptake explained 86% of the spatial and temporal variation in NO x release at an ecosystem level (for the reef crest and flat), which, along with the magnitude of PON p uptake, firmly implicates allochthonous phytoplankton as a major source of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Data are mean 6 SE, showing the number of values used in the calculations (n). See Table 2 focusing on specific habitats such as sediments (Capone et al 1992;Rasheed et al 2002;Al-Rousan et al 2004), coral cavities (Gast et al 1998;Scheffers et al 2004;Rasheed et al 2006), or micro atolls (Steven and Atkinson 2003), but the relevance of these habitat-specific rates at the scale of a reef community or ecosystem remains difficult to discern (Table 6). The release rates that were estimated in the present study, by assuming gross nutrient uptake was mass-transfer limited (J 2 MTL ), were on the same order as those documented in coral cavities and micro atolls, but were an order of magnitude higher than observed over carbonate sediments (generally a net sink; Wild et al 2005;Eyre et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond a few centimetres, mixing processes will dilute any signal (e.g. mucus, nutrients, associated bacteria, viruses, phytoplankton and zooxanthellae) exuded from the coral (Gast et al, 1998). Indeed, water column bacteria populations appear to be dissimilar to coral-associated bacteria (Rohwer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%